DISIPLIN PASAR, KRISIS PERBANKAN DAN PENJAMINAN SIMPANAN - Jati, Dian Purnomo; Setyawati, Sri Murni (Faculty of Economics and Business Universitas Jenderal Soedirman, 2012)
The purpose of this study is to identify the existence of market discipline in Indonesia.This research evaluate the interaction between market discipline and deposit insurance and the effect of crisis on market discipline. We use secondary data of bank’s financial report and panel regression analysis to test the hypothesis. The research found that depositors discipline banks by withdrawing deposits. Dummy crisis and dummy deposit insurance have significant effect to delta deposits. The result of data analysis show that market discipline exsist in Indonesia, there are found the correlation between market discipline, deposit insurance and banking crisis (risk).